An AI in the Triad: A Conceptual Model for Augmenting Collaborative Idea Construction with Generative AI - Siaw Hai Ng (Global READ Center, 2026)
The integration of Generative AI (GenAI) into educational settings necessitates a paradigm shift for collaborative learning, as established frameworks remain undertheorized for non-human agents. Extending the empirically grounded Collaborative Idea Construction (CIC) model and its stable peer roles (MKP, PA, DP), this paper proposes the AI- Enhanced CIC (AI-CIC) framework. GenAI is conceptualized as a novel 'Peer Apprentice' rather than a simple tool. This intervention reshapes human social architecture, transforming the Peer Assistant into an 'AI Validator' and elevating the More Knowledgeable Peer to a 'Metacognitive Facilitator.' Consequently, the collaborative workflow is hypothesized to become more linear. The AI-CIC model offers a theory-driven framework with testable propositions regarding emergent socio-technical roles and workflow shifts. It provides a foundation for future empirical research and informs pedagogical strategies for facilitating critical human-AI interaction.